The Identification of Basic Music Learning Needs Students of Music Arts Study Program Solfeggio Courses - Salafiyah, Nafik; Kevin, Kristian (Universitas Negeri Semarang, 2021)
To improve the quality of learning music in addition to ability and skills are also needed awareness of the requirements behind the success of students in learning music. The first step to learn the music before plunging into the skill of the instrument started by learning music basics first. To find out the problems faced by the students and how large the scope of the requirements needed by the students to support and simplify the learning of basic music and how to cope with them. The method that used in this research is qualitative method. The data collection techniques include interviews, observation, and documentation. The analysis data technique that used is reduction stage, data presentation, and verification or conclusion. The result of the research states that found some identification requirements to learn basic music involve Milleu, Man, Method, Machine, Money, and Material. Where each requirement should be understood and noticed by the students in order to optimize the mastery of basic music in the Solfeggio course